Japanese Notice - Spartan Daily:::::::::
An invitation to students to attend a meeting to learn more about plans to move Japanese American students and their families to prison camps. It is notable that the language used to describe incarceration includes words such as evacuation and relocation. (Spartan Daily, May 21, 1942)